A company's credit rating in Slovenia - Gornjak, Mojca (Advances in business related scientific research journal, 2025)
A company's ability to pay back its obligations was the main purpose of the credit rating at first, but it nowadays takes into account a wider range of elements. It relates to evaluating business excellence, the reliability of the organisation, its public reputation, and the supervision of business partners. A company's credit or financial rating is determined by analysing the financial performance of the preceding fiscal year. The research relies on a qualitative methodology, using a case study approach to calculate and compare the credit rating using three credit rating scores from Slovene rating agencies. The credit rating research is conducted by using accounting data extracted from financial statements. Every credit rating agency has certain criteria or indications to determine the credit rating. We understand that the credit rating score has been determined by the number of financial indicators or ratios used to calculate credit rating
Keywords: business indicators and ratios; calculation of credit rating; credit rating; methodology of credit rating